2015
DOI: 10.1016/j.jcrc.2015.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography in the intensive care setting can be used to detect changes in the quality and quantity of muscle and is related to muscle strength and function

Abstract: Muscle wasting occurs rapidly in the ICU setting. Ultrasonography is a useful surrogate measure for identifying future impairment. Vastus intermedius may be an important muscle to monitor in the future because it demonstrated the greatest change in muscle quality and had the strongest relationship to volitional measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
349
11
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 334 publications
(423 citation statements)
references
References 36 publications
24
349
11
12
Order By: Relevance
“…In our study, muscle wasting occurred earlier than reported in the literature: a previous study found that the cross sectional area of the rectus femoris muscle significantly decreased in the first 7 days of admission, whilst showing no changes in the first 3 days [10]. Further loss of muscle thickness has also been related with loss of muscle function on discharge from critical care [20]. …”
Section: Discussionsupporting
confidence: 50%
“…In our study, muscle wasting occurred earlier than reported in the literature: a previous study found that the cross sectional area of the rectus femoris muscle significantly decreased in the first 7 days of admission, whilst showing no changes in the first 3 days [10]. Further loss of muscle thickness has also been related with loss of muscle function on discharge from critical care [20]. …”
Section: Discussionsupporting
confidence: 50%
“…Interstitial lung abnormalities have been associated with decreased measures of pulmonary function and 6-minute-walk distance, increased respiratory symptoms, and genetic abnormalities, suggesting they may represent an early or mild form of pulmonary fibrosis (1). They have also recently been associated with an increased risk of death, specifically, death from respiratory failure (2). Patients with fibrotic lung disease can develop acute respiratory failure due to an exacerbation of their underlying disease.…”
Section: Interstitial Lung Abnormalities Are Associated With Acute Rementioning
confidence: 99%
“…A lower SMD was associated with increased lipid infiltration in muscle biopsies and poor clinical outcomes in non-ICU populations [1214]. Additionally, a recent study in critically ill patients using ultrasound of the quadriceps muscle found that not only a decrease in muscle quantity but also increased muscle echogenicity was related to a decrease in muscle function [15]. An increased amount of IMAT as assessed on CT scans has been associated with decreased muscle function and increased (systemic) inflammation in non-ICU populations [16, 17].…”
Section: Introductionmentioning
confidence: 99%